2008
DOI: 10.1080/14622200701767795
|View full text |Cite
|
Sign up to set email alerts
|

Smoking behavior and risk perception among the parents of infants in the neonatal intensive care unit

Abstract: The goal of this study was to explore the prevalence of smoking and attitudes and behaviors relevant to smoking cessation among parents of babies treated in a neonatal intensive care unit (NICU). Participants were 235 mothers and 83 fathers of infants admitted to the NICU of a large, university-based hospital. The 38-item survey included questions that assessed smoking status (current, former, never-smoker), motivation to quit, perceived health risks from smoking, and whether or not they received smoking cessa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
20
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 32 publications
(35 reference statements)
1
20
0
Order By: Relevance
“…Interventions by health care providers in the NICU are positively associated with increased parental understanding of the health risks of smoking to their infants and increased their motivation to quit. 31 Winickoff et al 32 have demonstrated the feasibility of implementing a strategy aimed at reducing smoking among parents during the postpartum hospitalization. Our study provides further evidence that the postpartum period is a time when mothers with a history of smoking may be responsive to encouragement and support to remain smoke free.…”
Section: Discussionmentioning
confidence: 99%
“…Interventions by health care providers in the NICU are positively associated with increased parental understanding of the health risks of smoking to their infants and increased their motivation to quit. 31 Winickoff et al 32 have demonstrated the feasibility of implementing a strategy aimed at reducing smoking among parents during the postpartum hospitalization. Our study provides further evidence that the postpartum period is a time when mothers with a history of smoking may be responsive to encouragement and support to remain smoke free.…”
Section: Discussionmentioning
confidence: 99%
“…(14,19) A study that evaluated the knowledge that 318 parents of children treated in an ICU had regarding smoking revealed that 70% of the parents believed that smoking could affect the health of children. (20) The current level of knowledge regarding smoking can be improved by means of health promotion campaigns in schools, at health care facilities and in the mass media. (1,(21)(22)(23) The present study showed that the lack of knowledge regarding smoking is associated with a lower level of education, which shows that it is necessary to improve the access that the general population has to information.…”
Section: Discussionmentioning
confidence: 99%
“…46,47 A survey of parents whose infants were admitted to the neonatal intensive care unit (NICU) reported that more than 70% said smoking was only ''a little'' or ''somewhat'' harmful to their infant. 48 Clearly, there is a gap or lack of maternal knowledge on the effects of infant exposure to second-hand smoke, and there remains a chasm in efforts to educate and support these women effectively to prevent harm to their fetus and infant. This gap in infant protection often extends to the spouse or partner, who may have smoked throughout the pregnancy, yet the issue of their stopping tobacco use was never broached.…”
mentioning
confidence: 99%
“…49 While spouses and significant others are more likely to be the smoker in the household, mothers are more likely to receive nicotine-dependency treatment. 48,50,51 The American Congress of Obstetrics and Gynecologists (ACOG) recommends obstetric healthcare providers screen all patients for their smoking status and offer tobaccodependence treatment. [52][53][54] The importance of early identification of mothers in need of tobacco-dependence treatment services is underscored by the evidence that successful efforts to stop smoking initiated early in pregnancy significantly improve pregnancy-related outcomes.…”
mentioning
confidence: 99%